Estudo da viabilidade de sistemas de captação solar de baixo custo constituídos por chapas de alumínio reaproveitáveis e tubos de polietileno - Rebelato, Gabriella (2022)
In this study, two low-cost solar collector systems were proposed and evaluated. Such systems have as main purpose, the reduction in the consumption of electric energy for heating water in a viable and sustainable way. The proposed collectors were built with plates from the disposal of printing industries, material with high thermal conductivity and high resistance to solar radiation, which were used as fins in the heating system. The aluminum plates were used to develop measures to mitigate the negative impacts of human actions on the environment through the environmentally correct disposal of waste, reusing discarded materials, generating socioeconomic benefits. Polyethylene tubes were also used in the collector, a material that has characteristics of easy commercial acquisition and high flexibility, allowing the reduction of the amount of accessories needed for the construction of the collector, thus reducing the points susceptible to failure. In one of the systems, polyethylene tubes in the “S” configuration were used for construction, so that the collector was fixed directly on the roof. The other proposed system was developed with the tubes in parallel, attached to a support to provide support to the system. Both systems were connected to a thermal reservoir located in a higher vertical position, in order to allow the thermosiphon to occur. The experiments were performed from measurements of the temperature variation of the fluid in the boiler in periods between december and march. The results showed the feasibility of the proposed equipment to heat the fluid. For the “S” configuration collectors, thermal gains greater than 30% of the fluid were obtained in relation to the ambient temperature. For the collector with tubes in parallel, it was possible to observe that with only 0.86 m2 of solar capture area, the water in the boiler reached temperatures close to 40ºC, and a thermal efficiency of 39% (this efficiency is considered high for low-cost collectors). In general, the proposed collectors differ from others previously developed by presenting a smaller quantity of accessories in the pipes, as well as materials with high resistance to solar irradiation, and can therefore be considered a viable and sustainable alternative to be implemented in residences.